Notes on Threatened Raptors seen during a Landscape Survey in Jaisalmer District, Thar Desert, Rajasthan - Bora, Neelkanth; Mitra, Unmesh; Mohan, Anthargam; Bishnoi, Pankaj; Khan, Musa; Narwade, Sujit Shivaji (Journal of the Bombay Natural History Society (JBNHS), 2023)
New renewable energy projects are coming up rapidly in the area around Deg Rai Mata Oran, near Devikot, in Jaisalmer district, Rajasthan. Therefore, a rapid study was conducted with the help of the local people from December 2021 to February 2022, to document raptor mortality due to collisions with newly installed power lines. We found 12 such instances of raptor mortality by power lines. A total of 30 raptor species were recorded. Their distribution maps, relative abundance, and nesting records are provided in this paper. Out of the 30 species, three were Critically Endangered, two Endangered, and four Vulnerable, according to the IUCN (International Union for Conservation of Nature) RedList. Raptor congregations were found in comparatively safe, undisturbed parts of north-western and northern Jaisalmer, such as areas in control of the Border Security Force (BSF) and Indian Army, as well as in Desert National Park (DNP) and its surroundings.